2019
DOI: 10.5387/fms.2019-22
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism after the Fukushima Daiichi Nuclear Power Plant accident:causation or coincidence?

Abstract: Cryptorchidism (undescended testes) is among the most common congenital diseases in male children. Although many factors have been linked to the incidence of cryptorchidism, and testicular androgen plays a key role in its pathogenesis, the cause remains unknown in most cases. Recently, a Japanese group published a speculative paper entitled, "Nationwide increase in cryptorchidism after the Fukushima nuclear accident." Although the authors implicated radionuclides emitted from the Fukushima accident as contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…The latest radiological environmental contamination disaster caused by the Fukushima Nuclear Power Plant has resulted in the leakage of large quantities of radioactive particles, including 131 I, 134 Cs, and 137 Cs. The disaster also has aroused health concerns among the local residents regarding possibilities of low birth weight or preterm births, , malformed fetuses, , thyroid cancer, , and so on. Therefore, it has become imperative to develop stable, effective, and ultrahigh methods for capture and storage of radioiodine.…”
Section: Introductionmentioning
confidence: 99%
“…The latest radiological environmental contamination disaster caused by the Fukushima Nuclear Power Plant has resulted in the leakage of large quantities of radioactive particles, including 131 I, 134 Cs, and 137 Cs. The disaster also has aroused health concerns among the local residents regarding possibilities of low birth weight or preterm births, , malformed fetuses, , thyroid cancer, , and so on. Therefore, it has become imperative to develop stable, effective, and ultrahigh methods for capture and storage of radioiodine.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear disaster caused by Chernobyl in 1986 and later by Fukushima in 2011 have attracted serious attention on the efficient removal and reliable storage of radioactive nuclear wastes. These disasters also have aroused health concern on local residents regarding a possibility of low birthweight or preterm births, 1,2 malformed fetuses, 3,4 thyroid cancer 5,6 and others, which may be caused by the radioactive nuclear waste leakage. Radiological iodine ( 129 I and 131 I) is one of these main waste streams with half-lives of 8 days and 15.7 million years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They rejected the hypothesis that cryptorchidism increased in Japan due to the Fukushima Daiichi Nuclear Power Plant accident. 41 Hirai et al, employing the All Japanese Cardiovascular Surgery Database, revealed no increase in the number of patients with congenital heart disease from 2010 to 2013. 42 …”
Section: Discussionmentioning
confidence: 99%